The counteractive effects of interventions addressing mental fatigue on sport-specific performance among athletes: A systematic review with a meta-analysis - Sun, H.; Soh, K. G.; Mohammadi, A.; Toumi, Z. (Journal of Sports Sciences, 2024)
The deleterious consequences of mental fatigue (MF) on athletes in diverse sporting domains have been subject to extensive inquiry. However, the efficacy of interventions to counteract the effects of MF remains largely elusive. This review aims to evaluate the effects of counteractive interventions on the sport-specific performance of mentally fatigued athletes. Moreover, synthesizes the current evidence on which sports effectively counter the detrimental effects of MF with interventions, highlighting potential avenues for upcoming research. A systematic search was executed via Web of Science, Scopus, PubMed, and EBSCOhost, in addition to Google Scholar and references for grey literature. A meta-analysis was executed to compute effect sizes for different interventions with 13 qualified papers. Interventions include transcranial direct current stimulation, person-fit, mindfulness, glucose supplementation, caffeine mouth rinsing, and nature exposure showed potential to mitigate the detrimental effects on sport-specific performance, particularly in shooting accuracy (ES = 0.591; p = 0.001), decision-making accuracy (ES = 0.553; p = 0.006), and reaction time (ES = -0.871; p < 0.001), however, not in completion time (ES = -0.302; p = 0.182). This review underscores the unique roles of self-regulatory resources and directed attention. Nonetheless, a cautious interpretation of the findings is warranted given the paucity of investigations involving potential interventions in numerous other sports, such as volleyball, Australian football, cricket, and boxing.